Retrospective histopathological study of canine mammary gland tumours diagnosed from 2006 – 2012 in Universiti Putra Malaysia - Sahabi, Kabiru; Selvarajah, Gayathri Thevi; Mohamed Mustapha, Noordin; Kumar Sharma, Reuben Sunil; Dhaliwal, Gurmeet Kaur (Veterinary Association Malaysia, 2015)
Forty-eight canine mammary tumours (CMT) diagnosed at the Histopathology Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia, were reviewed retrospectively. Two control groups, one comprising all other cases involving female dogs and another group comprising only cases of neoplasia involving female dogs diagnosed in the laboratory over the same period of time were used for comparisons in this study. Fisher’s exact test and logistic regression were used to determine association between the factors and the risk of CMT. Thirty-nine (81.3%) of the tumours were diagnosed as adenocarcinoma, 8.3% (n=4) each, were the diagnoses for squamous cell carcinoma and mixed cell tumour. Adenoma had 2.1% (n=1). The prevalence of canine mammary gland tumours in this study is 39%. When CMT cases were compared with all other cases, significant association was observed with adult dogs (p = 0.032, logistic regression 0.012) and intact dogs (p= 0.009, logistic regression, 0.003). When CMT cases were compared with neoplasia cases, significant association was observed with pure breeds (p = 0.025) and intact dogs (p = 0.000034, logistic regression 0.00042). This study found that pure breed dogs, intact dogs and older dogs (> 5years) have higher odds of having CMT in Malaysian dog population.